¿Como podemos incorporar la gestión de la biodiversidad en el campo? - Damonte, María Jimena; Poliserpi, Maria Belen; Riera, Brenda Paola; Michard, Nicole Jacqueline; Landi, Lucas; Solari, Laura María; Sanchez, Marcela Ines; Garcia, Pilar Agustina; Fritz, Federico G.; Suarez, Romina Paula (AAPRESID, 2024)
Poster